2022
DOI: 10.1111/odi.14123
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia: A clinicopathological study and malignant transformation

Abstract: Objectives To assess the clinicopathological characteristics of a cohort of patients with oral leukoplakia (OL) managed in a Romanian dental hospital and to evaluate the risk of malignant transformation (MT). Materials and methods We conducted a hospital‐based retrospective study using the clinical charts of patients diagnosed with OL that had complete clinical and histopathological evaluation followed up for 1–16 years. Results From 120 included patients, 68 (56.7%) were females, and 71 (59.2%) were current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
11
1
Order By: Relevance
“…The proportion of malignant transformation reported in different literatures varies greatly. [19,20]. The overall malignant transformation proportion in this study was 14.6%, higher than that reported in previous literature.…”
Section: Discussioncontrasting
confidence: 63%
“…The proportion of malignant transformation reported in different literatures varies greatly. [19,20]. The overall malignant transformation proportion in this study was 14.6%, higher than that reported in previous literature.…”
Section: Discussioncontrasting
confidence: 63%
“…Aguirre-Urizar et al [5] found an overall proportion of MT of 9.8% (95% CI: 7.9-11.7). Tovaru et al [20] reported 7.5% malignant transformation in their 120 leukoplakias, being more frequent in women and in those with dysplasia. Schepman et al [21] described a 2.9% annual malignant transformation rate in their 166 patients and Warnakulasuriya et al [22] informed that 2.6% of OPMDs cases transformed to invasive cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Real premalignant changes on the cellular level are observed in severe dysplasia only. Researchers worldwide consider that transformation of dysplasia into cancer occurs approximately within a period of four to seven years (Brouns et al, 2014;Alsalem, 2019;Tovaru et al, 2022). Therefore, it is necessary to study not only on nuclear changes, nuclear-cytoplasmic ratio, and architectural disarrangement in dysplasia, but also the subcellular processes of oral epithelium, particularly the molecular components in nucleus and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%